The Reporting of Brigadier J Murder on Indonesian Police’s Official News Media: Corpus-Based Discourse Analysis - Salim, Irfan Hanify; Suhandano, Suhandano (Journal of Language Intelligence and Culture, 2023)
This study aimed to analyze the discourses in news articles regarding the Brigadier J murder reported by the Indonesian Police’s official news media & the attempts of the institution in framing the image of the Indonesian Police in handling the murder case through particular words used by the institution’s news media. Further, this study used the descriptive qualitative method as its methodological approach & the corpus-based discourse analysis method as its theoretical approach. The data in this study were taken from news articles from Indonesian Police’s official news media website. The results of the study showed that the relevant keyword used by Indonesian Police news media to frame the murder case of Brigadier J case is the word murder and or premeditated murder. Besides, the way Indonesian Police online news media frame the image of the institution is by distributing positive news about the institution, as well as designating the positions & titles within the names of the officials. Furthermore, the Indonesian Police news media is engaging several positive adjectives to distribute positive images regarding the Police’s accomplishment in handling the murder case of Brigadier J.